REPRODUCTIVE AUTONOMY, THE NON-IDENTITY PROBLEM, AND THE NON-PERSON PROBLEM - Disilvestro, Russell (Bioethics, 2009)
The Non-Identity Problem is the problem of explaining the apparent wrongness of a decision that does not harm people, especially since some of the people affected by the decision would not exist at all were it not for the decision. One approach to this problem, in the context of reproductive decisions, is to focus on wronging, rather than harming, one's offspring. But a Non-Person Problem emerges for any view that claims (1) that only persons can be wronged and (2) that the person-making properties allow for there to be human non-persons. Consider an individual human organism that is prevented from ever possessing the person-making properties. On person-only accounts of the victims of wronging, this organism cannot be wronged by anyone. Hence even individuals whose decisions prevent it from ever possessing the person-making properties cannot wrong it. But this is counter-intuitive. We can think of examples where a human organism is wronged by precisely those decisions that prevent it from possessing the person-making properties. The best solution to this problem, in the case where the person-making property is rational self-governance in pursuit of a meaningful life, is to adjust the concept of a person so that it refers, not merely to those with the immediate capacity for rational self-governance in pursuit of a meaningful life, but also to those with a higher-order capacity for such self-governance. Any solution to the Non-Identity Problem that focuses on wronging rather than harming should incorporate this sort of solution to the Non-Person Problem.